Theoretical study of the structures of Schiff base compounds and thermodynamic study of the tautomerism reactions by ab initio calculations - Ali Hossein Kianfar; Roghayeh Hashemi Fath (Egyptian Journal of Petroleum)
In this research, structures of M(BAE) (where M = VO(IV), Zn(II), Cu(II) and Ni (II), BAE = bis(acetylacetone)ethylenediimine), [Ni(BFE)], [Ni(BBE)] and [Ni(BCE)] (where BFE = bis(1,1,1-triflouroacetylacetone)ethylenediimine, BBE = bis(benzoylacetone)ethylenediimine and BCE = bis(3-hloroacetylacetone)ethylenediimine) were determined by MP2 theoretical study. The thermodynamics of the tautomerism reactions was studied and the equilibrium constant of the reactions was calculated. The optimized molecular geometry and atomic charges were calculated using MP2 method with 6-31G(d) basis set and compared with the reported X-ray data. Nickel and copper complexes have a planar structure while the zinc structure shows a distorted square-planar N2O2 coordination geometry. The vanadyl structure has a square-pyramide N2O3 coordination geometry. Also the bond lengths and the bond angles were studied and compared.